Discovery and identification of infrared counterpart candidates of four Galactic centre low mass X-ray binaries - Curran, Peter; Chaty, S.; Zurita Heras, J. (EDP Sciences, 2011)
Context. The near infrared (nIR)/optical counterparts of low mass X-ray binaries (LMXBs) are often observationally dim and residein high source density fields which make their identification problematic; however, without such a counterpart identification we areunable to investigate many of the properties of LMXB systems.Aims. Here, in the context of a larger identification campaign, we examine the fields of four LMXB systems near the Galactic centre,in a bid to identify nIR/optical counterparts to the previously detected X-ray point sources.Methods. We obtain nIR/optical images of the fields with the ESO – New Technology Telescope and apply standard photometric andastrometric calibrations; these data are supplemented by Spitzer-GLIMPSE catalog data.Results. On the basis of positional coincidence with the arcsecond accurate X-ray positions, we identify unambiguous counterpartcandidates for XTE J1637-498, IGRJ17379-3747, IGRJ17585-3057 and GX9+1.Conclusions. We propose tentative nIR counterparts of four LMXBs which require further investigation to confirm their associationsto the X-ray sources.